Екологічні групи птахів Куликівського району Чернігівської області - Казимір О.А.; Казанник, Віталій Васильович (Київський національний університет імені Тараса Шевченка, 2024)
The avian fauna of the Kulykivka rayon in the Chernihiv oblast underwent thorough examination during the year 2024. Through meticulous observation, a comprehensive species inventory was compiled, documenting the presence and behavior of various avian species within the region. Additionally, ecological groups were delineated based on dietary habits and nest-building preferences, providing a nuanced understanding of the avian community’s ecological dynamics.
Ecological groups of birds in Kulykivka rayon Chernihiv oblast